Impermanence and Architecture. Ideas, Concepts, Words - Massimo Perriccioli (Agathón)
Temporariness, in its different ways of interpretation, is an emerging theme of the contemporary architectural research and raises questions about the effects of new technologies, both tangible and intangible, on ways of conceiving and realizing spaces for contemporary living. In reconsidering the concepts of stability and permanence within the process that establishes a new relationship between architectural space and time, a design approach oriented to the experimentation of innovative solutions and new structures of living is urged, towards a building philosophy in which construction becomes an act of conscious and continuously definable transformation, which arrange the time of technique to the life of man and re-establishes the importance of the temporal dimension as an environmental issue of the project.